1989
DOI: 10.1098/rspa.1989.0090
|View full text |Cite
|
Sign up to set email alerts
|

The equivalence between two perturbation methods in weakly nonlinear stability theory for parallel shear flows

Abstract: Two perturbation methods used in weakly nonlinear stability theory, namely, the method of multiple scales and the amplitude expansion method, are examined for their equivalence through formal analyses and numerical calculation of the Landau constants. The method of multiple scales is shown to give results equivalent to those obtained from the amplitude expansion formulation for slightly supercritical states if a normalization condition is applied to the fundamental mode. The convergence of the expansion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
(19 reference statements)
2
21
0
Order By: Relevance
“…Later Crouch and Herbert (1993) . The same problem was also considered by Sen and Venkateswarlu (1983) and Fujimura (1989Fujimura ( , 1991Fujimura ( , 1997) whose papers will be discussed below. Zhou (1982) developed an improved version of the classical Stuart-Watson method of 1960, assuming that both the amplitude A(t) and the angular frequency ω 1 (t) of the unstable wave disturbance vary with time.…”
Section: Evaluation Of Coefficients Of Amplitude Equations and Equilimentioning
confidence: 73%
See 3 more Smart Citations
“…Later Crouch and Herbert (1993) . The same problem was also considered by Sen and Venkateswarlu (1983) and Fujimura (1989Fujimura ( , 1991Fujimura ( , 1997) whose papers will be discussed below. Zhou (1982) developed an improved version of the classical Stuart-Watson method of 1960, assuming that both the amplitude A(t) and the angular frequency ω 1 (t) of the unstable wave disturbance vary with time.…”
Section: Evaluation Of Coefficients Of Amplitude Equations and Equilimentioning
confidence: 73%
“…Comparison of the values obtained with those given by the method of multiple scales showed that in all three cases the values of λ 2 and λ 3 , computed by this version of the method of center manifold, approach their values given by the method of multiple scales as the truncation level of the eigenfunction expansion increases. Hence the three papers by Fujimura (1989Fujimura ( , 1991Fujimura ( , 1997, taken together, show that Landau's Eq. (4.41b) given by two versions of the center manifold reduction scheme, the method of multiple scales, and the modified Watson amplitude-expansion method are equivalent to each other if the disturbance amplitude is defined in a consistent way.…”
Section: Evaluation Of Coefficients Of Amplitude Equations and Equilimentioning
confidence: 95%
See 2 more Smart Citations
“…Several equivalent weakly nonlinear formalisms can be found in the litterature (Stuart 1960;Watson 1960;Reynolds & Potter 1967;Herbert 1983;Fujimura 1989). Our formalism is along the lines of Herbert (1983).…”
Section: Appendix a Weakly Nonlinear Theorymentioning
confidence: 99%